Polysaccharides extracted from mulberry fruits (Morus nigra L.): antioxidant effect of ameliorating H2O2-induced liver injury in HepG2 cells - Xinle Li; Yanan Hua; Caixia Yang; Sijing Liu; Li Tan; Jinlin Guo; Yang Li (BMC, 2023)
Abstract Background Mori Fructus is an economical and readily available traditional Chinese medicine and food. Polysaccharides in Mori Fructus have clear antioxidant activity and have been found to alleviate oxidative stress (OS)-induced liver damage in experimental studies. The mechanism of regulation of cellular antioxidant activity by mulberry polysaccharides has been suggested to be Nrf2, but it is not clear whether the Nrf2 pathway is mediated by activation of other targets, and the exact process of effects in hepatocytes has yet to be elucidated. Methods In this study, the basic characterization of total polysaccharides extracted from mulberry fruits (Morus nigra Linn.) was analyzed. A model of oxidative damage induced by H2O2 in HepG2 cells was established. The levels of cellular oxidation-related markers, including ROS, SOD and Gpx, were then examined. Furthermore, Q-PCR and Western-blot were used to detect the expression of genes and proteins related to the PI3K/Akt-mediated Nrf2 signaling pathway. Results The results showed that a total mulberry polysaccharides (TMP) has a molecular weight of 57.5 kDa with a pyranose ring mainly composed of glucose (48.81%), galactose (22.79%) and mannose (18.2%). TMP reduced the accumulation of ROS in HepG2 cells after H2O2 treatment and modulated the activity of SOD and Gpx. Q-PCR and Western-blot showed that TMP could up-regulate the expression of p-PI3K, p-AKT, Nrf2, NQO1 and HO-1. Conclusions This study demonstrates that TMP can reduce ROS accumulation in H2O2-treated HepG2 cells and restore cell viability by activating the PI3K/AKT-mediated Nrf2 pathway. TMP may be a potent antioxidant agent that could slow down oxidative damage to the liver.